Backyard soccer drills [videorecording (DVD)] - Barbieri, Ernest; Fratello, Lou (Youth Sports Club, 2004)
Coach Lou Fratello presents drills for youth level soccer, with more than fifty creative backyard drills for the youth soccer athlete. Technical skills covered include fast footwork drills, shooting drills, passing drills, volley drills, goalie drills, and heading techniques. All these skills and more can now be practiced in the comfort of the backyard, making soccer challenging and fun for players, coaches, and parents.